Multi-Criteria Decision Making for Prioritizing Project Manager Skills according to Construction Project Success Factors - Mansor, Maysoon Abdullah (Engineering, Technology & Applied Science Research, 2025)
The possession of specific skills by the project manager is a critical factor in the success of construction projects at every stage of development. The objective of this research is to identify and prioritize the specific skills that a project manager must possess to ensure a successful construction project. A comprehensive theoretical review was conducted, leading to the identification of 22 soft skills and 10 technical skills that are essential for project managers to ensure the success of construction projects. A preliminary questionnaire was used to evaluate the relative importance and interrelationships among the identified skills. This was followed by an expert questionnaire, which was assessed utilizing two analytical methods: the Stepwise Weight Assessment Ratio Analysis (SWARA) for skills and the main success factors of the construction project, and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) for skills according to the success factors. The preliminary questionnaire revealed that all project manager skills were deemed to be of significant importance, with percentages ranging from 0.7 to 0.818. Additionally, a moderate to weak correlation was observed between soft skills, with values ranging from 0.005 to 0.686, while for technical skills, a medium correlation was observed (0.707). The top five skills were identified as coordination, general knowledge of project management, communication, dealing with others, and organization. The TOPSIS technique revealed the preference order of soft skills: coordination skill (0.98), supervision (0.552), and general knowledge of project management (0.473). Regarding the preference order of technical skills, the following were revealed: legal experience (0.672), oral skills and listening (0.369), and planning, strategic planning, and goal setting (0.359). The findings of this study assist those responsible for making decisions concerning the most essential skills required for a project manager and provide a framework for selecting a project manager based on these competencies.